Sime Darby Plantation: a study on factors influencing the customer awareness towards Sime Darby foods product / Norzi Ishak - Ishak, Norzi (Faculty of Business and Management, 2008)
This research is to study about factor influencing the customer awareness towards Sime Darby foods product on business market. The study was conducted in one of the largest plantation company in the world company which is, Sime Darby Berhad, specifically in Sime Darby Plantation marketing department. This research is to identify the solutions that faced by Sime Darby Plantation. The main problem faced is low customer awareness regarding the Sime Darby foods products that lead to difficulties in selling products that will affect the sales performance. Due to the problems, there are certain circumstances why the research objective was developed. First, is to examine the influence of promotion towards customer awareness. Second is to access the influence of brand name towards customer awareness Third objectives is to study the influence of staff attitude towards customer awareness and the last objective is to determine the influence of customer buying behavior towards customer awareness. The findings of the research state that all the variables, promotion, brand name, staff’s attitude and customer buying behaviour have a strong relationship with customer awareness and lead to the successful of sales. Overall, based on the findings, there are several recommendations that have been suggested in order to help or to improve the organization.